Solution of Scalar Riccati Differential Equation of Fractional Order - Subhi Fadhel, Fadhel; Hashim Jasim, Sabreen (Al-Nahrain Journal of Science, 2019)
The main objective of this paper is to generalize the scalar Riccati differential equation for factional order derivatives using Caputo definition, and then to find its approximate solution using the variational iteration method. The present work consists of the statement and the proof of the variational iteration formula and then prove of its convergent to the exact solution. Some illustrative examples are considered and simulated using Mathcad 15 computer program.